Ultrafast switch-on dynamics of frequency-tuneable semiconductor lasers - Iman Kundu (Nature Portfolio, 2018)
Single-mode, tuneable monolithic semiconductor lasers are important light sources for integrated photonics. Here, Kundu et al. observe the switch-on dynamics and mode competition of a terahertz quantum cascade laser and explain the behaviour with a carrier and photon transport model.